Предмет: Математика,
автор: zaremawinter20
Срочно!
С подробным решением!
Приложения:
Ответы
Автор ответа:
1
Ответ: 9,8
Автор ответа:
0
так как (a-b)*(a+b)=a^2-b^2
то (7у-7)(7у+7)=(7у)^2-(7)^2=49у^2-49
а (7у-7)(7у+7)-7у(7у+7)=49у^2-49-7у*7у-7у*7=
49у^2-49-49у^2-49у=-49у-49
при у=-1,2, -49у-49=-49*(-1,2)-49=49*1,2=49*1+49*0,2-49=9,8
ответ:9,8
то (7у-7)(7у+7)=(7у)^2-(7)^2=49у^2-49
а (7у-7)(7у+7)-7у(7у+7)=49у^2-49-7у*7у-7у*7=
49у^2-49-49у^2-49у=-49у-49
при у=-1,2, -49у-49=-49*(-1,2)-49=49*1,2=49*1+49*0,2-49=9,8
ответ:9,8
Похожие вопросы
Предмет: Химия,
автор: mydreamnumber1
Предмет: История,
автор: Cowlkett
Предмет: Геометрия,
автор: valerikolesnik80
Предмет: Алгебра,
автор: mysheva
Предмет: Математика,
автор: mania4